A Sosialisasi Sistem Jaminan Halal (SJH) Dalam Memperoleh Sertifikat Halal Di IKM Rembulan Kota Gorontalo: Sosialisasi Sistem Jaminan Halal (SJH) Dalam Memperoleh Sertifikat Halal Di IKM Rembulan Kota Gorontalo - Laksmyn Kadir (Madani: Jurnal Pengabdian Ilmiah, 2022)
Abstract The increase in the need for snacks has not been matched by the availability of production facilities and infrastructure that meet the halal and sanitation requirements. Most of the products do not meet the requirements and even look mediocre. This condition has led to high deviations; many cases of circulating expired cake products that do not meet the halal food requirements for domestic and export-import products have been found. This service aims to provide an understanding of halal policies under the provisions of LPPOM MUI. The method used is the principle of Adult Education (POD). In implementing the provisions of the fatwa, the socialization activity about halal policy to participants at the Rembulan IKM production house went smoothly and under the expected target, namely increasing awareness of owners and employees about how to understand and observe the tools and materials used in producing products that comply with halal standards so that these expectations can be achieved well.